DESIGN OF A GEOGRAPHIC INFORMATION SYSTEM (GIS) TO DETERMINE HOUSING LOCATIONS IN ASAHAN - Dwiki Ramadhan; Arridha Zikra Syah; Akmal (Informatika, Universitas Jenderal Soedirman, 2022)
The Housing and Settlement Office of Asahan Regency haven’t a system that can map the location of housing in the East Kisaran District, Asahan yet. The purpose of this study was to help the performance of the Asahan District Housing and Settlement Service and the community in obtaining information on the location of housing in East Kisaran District, Asahan. become faster, more efficient, and more complete in managing data in housing mapping digitally and online. This research method was carried out using qualitative research methods with stages consisting of observation, interviews, documentation, and literature study. This system was designed with the PHP programming language based on Codeigneter, the database system uses MySQL, and Google Maps API which can mapping the location of housing in Kisaran Timur District, Asahan. The result of this study was a website-based geographic information system that allows the public to obtain the information they need about housing in the East Kisaran District, Asahan.